Design of an optimized energy-efficient routing protocol for reliable wireless body area networks - Almutairi, Hissah; Alqahtani, Abdullah; S. Jabbar, Zinah; Fadhil Tawfeq, Jamal; Dheyaa Radhi, Ahmed; Soon JosephNg, Poh (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Energy limitation is one of the essential parameters in the design of a Wireless body area networks (WBANs) as it is important to improve the lifetime of the network. WBAN routing is an effective approach for establishing energy efficiency sets and assign time slots for the network. Many algorithms that deal with interference model treats the whole WBAN as a minimum interference unit and increase their lifetime cycle. In this research, we report an effective low-energy adaptive clustering hierarchy (LEACH) routing protocol using MATLAB simulation and related C++ simulation codes to enhance the overall performance of the network by improving the energy efficiency and network lifetime cycles. Furthermore, the study sheds light up on the comparison of the protocol and proposes a modified protocol for WBAN. Based on the results obtained from conducting different configurations in the proposed design, the base station should be situated near the network to insure high network performance.